The detection of antibiotics in raw milk samples in bursa region - Canan Dokuzlu; Mustafa Tayar (Eurasian Journal of Veterinary Sciences)
In this study a total ol 150 milk samples were tested for thepresence ol antibiotics by intertest and agar diffusion methods. First, the intertest method and than agar dilfusion tests were applied to the samples. Bacillus megatherium ATCC 9855 for chloramphenicol, Basillus stearothermophilus var, calidaloctis C-953 for penicilhne and Bacillus subtıüs ATCC 6633 for tetracyclines were used as a sensilive strains in agar diffusion test. The results of the intertest method have showed lhai 40 (26.6 %) ol them gave suspicious results and 27 samples (18.00 %) were negative for antibiotic residues. According to the agar diffusion test results, 27 (18.00 %) of samples were positive for penıcılline, 11 (7.33 %) ol them for tetracyclines and 2 (1.33 %) of them for chloramphenicol. A total of 110 (73.33 %) samples no antibiotic residues were detected.